2012
DOI: 10.1039/c2nr30415e
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor interaction with gold nanoparticles

Abstract: We report on a systematic investigation of molecular conjugation of tumor necrosis factor-α (TNF) protein onto gold nanoparticles (AuNPs) and the subsequent binding behavior to its antibody (anti-TNF). We employ a combination of physical and spectroscopic characterization methods, including electrospray-differential mobility analysis, dynamic light scattering, polyacrylamide gel electrophoresis, attenuated total reflectance-Fourier transform infrared spectroscopy, fluorescence assay, and enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 74 publications
2
36
0
Order By: Relevance
“…4B). This result indicated that some of the untreated unlabeled TNFα had dissociated to the monomeric form during the analysis, as has been reported previously with SDS-PAGE analysis [29, 30]. However, cross-linked unlabeled TNFα showed a single band at the trimer location (Fig.…”
Section: Resultssupporting
confidence: 86%
“…4B). This result indicated that some of the untreated unlabeled TNFα had dissociated to the monomeric form during the analysis, as has been reported previously with SDS-PAGE analysis [29, 30]. However, cross-linked unlabeled TNFα showed a single band at the trimer location (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Because NPs have high surface free energy, in order to decrease NP surface energy [51], many kinds of protein can be adsorbed on the surface of Au NPs with distinct binding affinities [52, 53]. When exposed to biological fluids or microenvironments, Au NPs can contact and adsorb a variety of proteins such as ubiquitin [54, 55], serum albumin [56, 57], tumor necrosis factor [58, 59], cytochrome C [29], fibrinogen [60], or polypeptides [61]. Usually, the high abundance proteins first arrive at and adsorb on the surface of NPs, but they will be eventually replaced by high-affinity proteins to form NP–protein complexes [62].…”
Section: Au Np–protein Interactionsmentioning
confidence: 99%
“…Recent evidence suggests that proteins adsorbed to surfaces aggregate [147,148]. Since these aggregated proteins may then desorb, one might reasonably wonder, how these desorbing 74 proteins may impact size distributions obtained with ES-DMA, an aspect that has never been studied before.…”
Section: Introductionmentioning
confidence: 99%